An update on pathophysiological mechanisms related to idiopathic oro‐facial pain conditions with implications for management. (8th December 2014) - Forssell, H.; Jääskeläinen, S.; List, T.; Svensson, P.; Baad‐Hansen, L.
Summary Chronic oro‐facial pain conditions such as persistent idiopathic facial pain (PIFP), atypical odontalgia (AO) and burning mouth syndrome (BMS), usually grouped together under the concept of idiopathic oro‐facial pain, remain a diagnostic and therapeutic challenge. Lack of understanding of the underlying pathophysiological mechanisms of these pain conditions is one of the important reasons behind the problems in diagnostic and management. During the last two decades, neurophysiological, psychophysical, brain imaging and neuropathological methods have been systematically applied to study the trigeminal system in idiopathic oro‐facial pain. The findings in these studies have provided evidence for neuropathic involvement in the pathophysiology of PIFP, AO and BMS. The present qualitative review is a joint effort of a group of oro‐facial pain specialists and researchers to appraise the literature on idiopathic oro‐facial pain with special focus on the currently available studies on their pathophysiological mechanisms. The implications of the findings of these studies for the clinical diagnosis and treatment of idiopathic oro‐facial pain conditions are discussed.